Has the German reunification strengthened Germany's national innovation system? Triple helix dynamics of Germany's innovation system - Sæung-gyu Yi; Bogang Jun (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2016)
This paper investigates whether the German reunification strengthened the country's national innovation system, using the Triple Helix model. In particular, it assesses the various dimensions of the innovation system by analyzing co-authorship networks from 1973 to 2014. Despite the series of policies promoting collaboration between the two regions and the rise in the number of regional collaborations and in the number of papers, the results show that the national innovation system of Germany has worsened since the reunification in 1990, and the role of government is critical in encouraging collaboration. Finally, this paper uses survey data on the type of Triple Helix configuration that actually occurred in East Germany as a robustness check.
urn:nbn:de:bsz:100-opus-12856
Keywords: 330; Triple Helix model; German reunification; National innovation system